An Examination of the Psychometric Properties of Some Commonly Researched Individual Differences, job, and Organizational Variables in two Cultures - Sekaran, Uma; Martin, Harry J. (Journal of International Business Studies, 1982)
This study examines the transferability and applicability of selected measures of individual differences, job, and organizational climate factors across two cultures. Questionnaires were administered to a sample of 267 white-collar bank employees in the U.S. and 307 bank employees in India. The individual difference dimensions examined were four manifest needs, sense of competence, and locus of control. The job factors included variety, autonomy, identity, and feedback. The organizational climate factors related to communication, stress, participation in decision making, and self-esteem from the workplace. The data were analyzed for internal consistency, dimensionality, and criterion-related validity. The results showed that the job and organizational climate measures were more reliable and were related more consistently to the criterion measures than the individual difference measures both within and across cultures. The results suggested that psychometrically sound measures may be transferable to other cultures.